2008
DOI: 10.1080/09064710701718296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative economic analysis for production of naked vs. conventional oat

Abstract: The greatest barrier to the use of oat as an animal feed is its high hull content. In spite of its excellent fat and amino acid composition in animal feed use, as far as nutritional value is concerned, the total energy yield of oat is weaker than that of other cereals because of the hulls which have an energy yield like that of straw, so the use and cultivation of oat has remained behind that of plants richer in energy. There are two ways to improve the low energy yield from the cultivation of oat: one is to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This outcome could be due to the removal of the low digestible hull and its negative effect on intestinal digestibility (Welch et al, 1983). On the other hand, the lower digestibility of whole oat grain was attributed to the extensive ester cross-link bonds between polysaccharides and lignin in oat hull and its high fiber content (Yu et al, 2005;Kirkkari, 2008). The results of the mobile bag study showed that lower TTD of CP in the intact oat could be related to the low digestibility of hull protein in addition to its negligible CP concentration.…”
Section: Digestion Of Cp and Aa In The Small Intestinementioning
confidence: 99%
“…This outcome could be due to the removal of the low digestible hull and its negative effect on intestinal digestibility (Welch et al, 1983). On the other hand, the lower digestibility of whole oat grain was attributed to the extensive ester cross-link bonds between polysaccharides and lignin in oat hull and its high fiber content (Yu et al, 2005;Kirkkari, 2008). The results of the mobile bag study showed that lower TTD of CP in the intact oat could be related to the low digestibility of hull protein in addition to its negligible CP concentration.…”
Section: Digestion Of Cp and Aa In The Small Intestinementioning
confidence: 99%
“…Genomic DNA was extracted from 15-20 coleoptiles of several day old seedlings of each breeding form following the CTAB procedure (Doyle and Doyle, 1987). grain quality could be achieved by breeding for reduced husk content or breeding high yielding naked oat cultivars (Kirkkari, 2008). Naked oat refers to a variety with lemma and palea separating from the grains during threshing.…”
Section: Plant Materials and Dna Extractionsmentioning
confidence: 99%
“…Moreover, the husk plays a crucial role in protecting the groat from damage (Burrows, 1986) and pathogenic attack (Ronald et al, 1999). Nevertheless, dehusked conventional oat, does not achieve comparable economic result as naked one, as dehusking costs and disposition of the husk waste is considerably large (Kirkkari, 2008). Naked oat could be a suitable alternative to conventional oat.…”
Section: Plant Materials and Dna Extractionsmentioning
confidence: 99%
See 1 more Smart Citation